Fabrication, characteristics and hydrothermal stability of methyl-modified Ni-Co/SiO2 membranes for H2/CO2 separation. (February 2023) - Yan, Mengyu; Yang, Jing; Mu, Ruihua; Guo, Yingming; Cui, Xinshui; Song, Jinghua
Abstract: Silica membranes possess gas separation characteristics, but their undesirable performances and poor hydrothermal stabilities hinder the application in industrial gas treatments. To solve the problems, we have devised a new membrane preparation method involving methyl group modification and nickel-cobalt doping. In this paper, methyl-modified silica (MSiO2 ) and nickel-cobalt-doped methyl-modified silica (Nix Co0.08−x /MSiO2, x = 0, 0.024, 0.04, 0.056 and 0.08) materials and membranes were synthesized using the sol-gel technique. The physical-chemical properties of materials were characterized by FTIR, XRD, TEM, N2 adsorption-desorption and SEM. The H2 permeances and permselectivities of membranes were evaluated with pressure difference, temperature, Ni/Co content and hydrothermal stability as the inferred factors. In Ni-Co/MSiO2 materials, nickel and cobalt elements were found in the form of Si-O-Ni/Si-O-Co bonds and NiO/CoO. The H2 permeance and H2 /CO2 permselectivity of the Ni0.024 Co0.056 /MSiO2 membrane were 7.6 × 10 −7 mol m −2 Pa −1 s −1 and 113.5, respectively, which were 2.1 and 2.8 times higher than the MSiO2 membrane at 0.3 MPa and 200 °C. After steam treatment and regeneration, the Ni0.024 Co0.056 /MSiO2 membrane increased from the original values in the H2 permeance and H2 /CO2 permselectivity, while the MSiO2 membrane decreased. The final results revealed that Ni-Co/MSiO2 membranes possessed excellent H2 /CO2 permselectivity and hydrothermal stability. Graphical Abstract: ga1 Highlights: Methyl-modified silica (MSiO2 ) and nickel-cobalt-doped methyl-modified silica (Ni-Co/MSiO2 ) materials and membranes were synthesized under N2 atmosphere. The physical-chemical properties of materials were characterized by FTIR, XRD, TEM, N2 adsorption-desorption and SEM. The H2 permeances and permselectivities of membranes were evaluated with pressure difference, temperature, Ni/Co content and hydrothermal stability as the inferred factors. The Ni-Co/MSiO2 membranes possessed excellent H2 /CO2 permselectivity and hydrothermal stability.